TANGGUNG JAWAB PIDANA NOTARIS DALAM KEDUDUKANNYA SEBAGAI PEJABAT PEMBUAT AKTA - Amiruddin, Amiruddin (Jurnal Media Hukum, 2015)
Notary is a profession which honors moral values so that every act violating the law conducted by the notaries in performing their duty must be legally liable. In serving their function, it is possible for them to make various kinds of mistake such as administrative error which results in administrative liability, civil fault which causes civil liability, and criminal defect which begets criminal liability. The criminal liability of the notary is based on the criminal law principle geen straf zonder schuld (there is no convict without any offense). If the notaries commit an act against the law and they are able to be responsible for it, either it is done intentionally or unintentionally, they have to receive the legal consequence without any mercy. Therefore, the parameters of the criminal liability are the act against the law and the offense. Those make it possible for the notaries to be condemned.Â